Contextual Meaning Of Arab Commentators When Commenting On European Football Broadcasts - Abrar, Atthariqul; Syamsurrijal, Muhammad (TSAQOFIYA : Jurnal Pendidikan Bahasa dan Sastra Arab, 2024)
The aim of this research is to determine the meaning of Arabic interpretive texts using a contextual theory approach. This research relies on library resources, including data collected from the premium Arabic channel Bein Sport, with two well-known commentators, namely Uṣām Asy-Syawālī and Hāfiẓ Ad-Darājī. In this study, researchers found at least forty sentences containing the phrase "Arab Commentator" on the Arabic language channel "Bein Sport Premium" that contain contextual meaning. The results of this research demonstrate that contextual theory is highly relevant in interpreting Arabic texts. In these findings, researchers obtained four categorizations of contextual meaning from two prominent commentators, Uṣām Asy-Syawālī and Hāfiẓ Ad-Darājī. These categorizations include language, taste, social culture, and situations and conditions. According to Uṣām Asy-Syawālī's interpretation, there are seven meanings in the aspect of taste, four meanings in the socio-cultural aspect, five meanings in the aspect of language, and four meanings in the aspect of situations and conditions. Hāfiẓ Ad-Darājī, on the other hand, suggests that there are four meanings in the aspect of taste, four meanings in the aspect of language, and twelve meanings in the aspect of situations and conditions. Asbtrak Penelitian ini bertujuan untuk mengetahui makna suatu teks Komentator bahasa Arab melalui pendekatan teori Kontekstual. Penelitian ini menggunakan penelitian kepustakaan yang datanya dikumpulkan melalui kanal siaran Bein Sport premium Arab dari kanal Bein sport Premium Arab, dengan dua juru komentator kondang yaitu Uṣām Asy-Syawālī dan Hāfiẓ Ad-Darājī. Adapun hasil dari penelitian ini adalah setidaknya ada 40 ungkapan dari komentator Arab yang bermakna kontekstual. Dalam temuan tersebut, peneliti memperoleh empat kategorisasi makna kontekstual dari dua mufasir terkemuka Uṣām Asy-Syawālī dan Hāfiẓ Ad-Darājī, yaitu pada aspek bahasa, rasa, sosial budaya, serta situasi dan kondisi. Dalam tafsir Uṣām Asy-Syawālī terdapat tujuh makna pada aspek rasa, empat makna pada aspek sosial budaya, lima makna pada aspek bahasa, dan empat makna pada aspek situasi dan kondisi. Menurut ahli tafsir Hāfiẓ Ad-Darājī, terdapat empat makna pada aspek rasa, empat makna pada aspek bahasa, dan dua belas makna pada aspek situasi dan kondisi.